Genetic progress with reciprocal recurrent selection for interpopulation hybrids of maize - Reis, Matheus Costa dos; Souza, João Cândido de; Ramalho, Magno Antônio Patto; Guedes, Fernando Lisboa; Santos, Pedro Henrique Araújo Diniz (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the genetic progress obtained in interpopulation hybrids with the reciprocal recurrent selection. During the 2005/2006 planting season, maize (Zea mays) interpopulation crosses from three selection cycles (0, 1 and 2) initiated in 2003, single-cross parental hybrids and the double-cross F1 hybrid were evaluated in randomized blocks with five replicates, at two locations. In the next planting season, only interpopulational hybrids from cycles 0 and 2 were evaluated under the same conditions, with 40 replicates per location. The interpopulation hybrid had a yield performance equivalent to that of the best single-cross parent in few selection cycles. The estimates of genetic progress per cycle were of 7.9% (or 0.7 Mg ha-1) for unhusked ear yield and of 3.5% for prolificacy. It is possible to infer that the reciprocal recurrent selection effectively improves the yield of interpopulational hybrids obtained from F2 generations of single-cross maize hybrids.